2002
DOI: 10.3233/jae-2002-429
|View full text |Cite
|
Sign up to set email alerts
|

Development of ID-blade slicer monitoring system for cutting 12-inch silicon ingot

Abstract: This work is concerned with an experimenta1 study on online measurernent ofthe states gf D saw blade cutting a 12-inch crystal ingot. An online monitoring system consisting of a 3-axis gi,e:?,ei.,c,tn' :,ge.",s,2'i,a,th.r,eg,Za."8dVtr,'.ai,,fi."%ri,.a.,dg'gt,t.a..i.ogcigLoa.po,pe.eq8,c;:;gl,gutej.w,a,s..de{/%igpld6 decomposed in three frequency regions to evaluate the blade extension circurnstance, the sharpqess. of blade edge and the interference between blade and ingot The proposed D-Blade slicer momtormg sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The researches on the behavior of the ID saw blade have been carried out mainly on stress and vibration analysis [1,4], and manufacturing technology of ID saw blade [5,7]. S. Chonan et al (1993) analyzed the stress distribution in a working ID blade slicing a crystal ingot [1], and found that the initial tension had a significant effect on the natural frequencies of the blade, while the lateral deflection of the blade was much affected by the lateral reaction force from ingot [2].…”
Section: Inroductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researches on the behavior of the ID saw blade have been carried out mainly on stress and vibration analysis [1,4], and manufacturing technology of ID saw blade [5,7]. S. Chonan et al (1993) analyzed the stress distribution in a working ID blade slicing a crystal ingot [1], and found that the initial tension had a significant effect on the natural frequencies of the blade, while the lateral deflection of the blade was much affected by the lateral reaction force from ingot [2].…”
Section: Inroductionmentioning
confidence: 99%
“…Z.W. Jiang et al (2001Jiang et al ( /2002 proposed ID -blade slicer monitoring system to online measure the vibration states of ID saw blade and evaluate its performance [4]. For improving the performance of ID saw blades, F.Y.…”
Section: Inroductionmentioning
confidence: 99%
“…There are two main processing methods for hard and brittle material slicing: diameter sawing [ 1 , 2 , 3 ] and wire sawing [ 4 , 5 , 6 , 7 ]. The diameter sawing methods broadly include inner diameter sawing [ 8 , 9 , 10 ] and external diameter sawing [ 11 , 12 ]. Compared with wire sawing and external diameter sawing, inner diameter sawing technology has greater advantages in small batch production and wafer roundness control, and it is more suitable for the processing of ceramics with moderate or short lengths [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Under normal circumstances, there are two main processing methods for ceramics slicing: diameter sawing technology [6][7][8] and wire sawing technology [9][10][11][12]. The diameter sawing technology is divided into inner diameter sawing technology [13][14][15] and external diameter sawing technology [16,17]. Compared with the other two processing methods, the inner diameter sawing technology has greater advantages in small batch production and wafer roundness control, and it is more suitable for the processing of ceramics with moderate or short lengths [18].…”
Section: Introductionmentioning
confidence: 99%